Equity valuation : WestJet Airlines - Salib, Michelle (2019)
The purpose of this dissertation was to determine if a discrepancy was present in the market value of WestJet Airlines (WJA.TO) relative to its computed intrinsic value. WJA.TO is one of two major airlines that services the Canadian market and has experienced significant growth in its 25 years of tenure. As such, they appear to have entered into a state of maturity which now prompts the question, “what is their true value”. To thoroughly answer this question, an in-depth analysis of past market conditions as well as future market expectations and the competitive landscape were assessed in conjunction with WestJet’s historical performance. The Discounted Cash Flow method was used in tandem with a Relative Valuation approach to arrive at a value of $35.41/share CAD with the current share price hovering at $31/share CAD. Because the current $31/share was a market reaction to the Onex offer, the recommendation would be to Hold the stock as investment theory dictates that price is unlikely to move beyond that $31/share threshold. This valuation was directly compared to two analysts’ reports, one preceding the Onex deal and one proceeding it, with a $35/share price more closely aligning with the analyst report following the announcement.